Human sweet, umami and bitter taste receptors: From decoders of taste perception to sentinels of systemic metabolism and health - Yuxiang Gu; Yixuan Cui; Kangli Guo; Guoping Zhao; Xing Li; Weixi Yang; Yanbo Wang (Trends in Food Science & Technology, 2026)

Impact of metals exposure on lung function and serum club cell secretory protein among schoolchildren: A mixture and mediation analysis - Jie Li; Meili Shen; Ting Wang; Xiao Zhang; Wen Gu; Mengmeng Xu; Tongjin Yang; Jie Cui; Xin Xia; Guoping Chen; Siyu Zheng; Haoying Yang; et al. (Journal of Hazardous Materials, 2024)

Instantaneous detection and location of contaminant sources in intelligent buildings: A distributed Kalman filter scheme - Chen Ma; Aibing Qiu; Xiaojing Peng; Juping Gu; Guoping Lu (Energy and Buildings, 2024)

Multiphase riveting structure constructed by slight molybdenum for enhanced P3/O3 layer-structured oxide cathode material - Hailong Ren; Xuan-Wen Gao; Dongrun Yong; Zhaomeng Liu; Xuanchen Wang; Guoping Gao; Hong Chen; Qinfen Gu; Wen-Bin Luo (Chemical Engineering Journal, 2024)

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Holocene range collapse of giant muntjacs and pseudo‐endemism in the Annamite large mammal fauna - Samuel T. Turvey; James Hansford; Selina Brace; Victoria Mullin; Shengxiao Gu; Guoping Sun (Journal of Biogeography, 2016)
Aim To clarify the post‐glacial biogeography of the Annamite and eastern Chinese ungulate faunas, and determine whether current understanding of Asian mammalian biogeography is biased by pseudo‐extinctions and pseudo‐endemism associated with a historical extinction filter. Location Modern‐day specimens of giant muntjac ( Muntiacus vuquangensis ) from the Annamite Mountains of Laos and Vietnam were compared with zooarchaeological specimens of extinct giant muntjac ( M. gigas ) from eastern China, and with a reference sample of northern red muntjac ( M. vaginalis ) from China, Southeast Asia and South Asia. Methods We analysed a data set of antler measurements using Multivariate analyses of variance ( MANOVA s), principal component analyses ( PCA s) and scaling relationships, to quantify morphometric variation between extinct and living giant muntjacs in relation to variation shown by a different sympatric large‐bodied muntjac species. We also attempted ancient biomolecule analysis of Holocene samples from China. Results Although the combined giant muntjac sample can be differentiated from the reference red muntjac sample in all of our multivariate morphometric analyses, no significant differences are shown between extinct and living giant muntjacs using any analyses, matching the pattern seen when comparing conspecific red muntjac samples from across the same geographical region. Main conclusions We find no support for recognizing extinct and living giant muntjacs as distinct taxa, and post‐glacial populations from China and the Annamites should probably all be referred to M. gigas . The likely conspecificity of giant muntjacs across Eastern and Southeast Asia demonstrates that current‐day Asian mammalian biogeography has been shaped by an extinction filter and challenges the idea that the Annamite region represents a cradle of evolution; instead, it may represent a refuge of diversity for some taxa, preserving remnant pseudo‐endemic populations of species that have been extirpated across other parts of their former ranges.

Statistical characteristics and formation mechanism of the Lanyu cold eddy - Ruili Sun; Yanzhen Gu; Peiliang Li; Lei Li; Fangguo Zhai; Guoping Gao (Journal of Oceanography, 2016)

Viral metagenomics analysis of picobirnavirus-positive feces from children with sporadic diarrhea in China - Guangming Sun; Qinbo Zang; Yu Gu; Guoping Niu; Chen Ding; Peiying Zhang (Archives of Virology, 2016)